2012
DOI: 10.5665/sleep.1586
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Insomnia: the Role of Objective Short Sleep Duration and Mental Health

Abstract: Objective short sleep duration and mental health problems are the strongest predictors of persistent insomnia. These data further support the validity and clinical utility of objective short sleep duration as a novel marker of the biological severity of insomnia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
87
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 35 publications
7
87
1
Order By: Relevance
“…These findings further support that objective short sleep duration is a biological marker that predicts both the severity 2 and the natural course of the disorder. 5,6 We agree with Dr Kawada 1 that the use of polysomnographic measures provides strong validity for the findings reported in our study and that future longitudinal studies using longer and multiple followups should further examine the relationship among the natural history of insomnia, objective sleep duration, and cardiovascular risk.…”
supporting
confidence: 86%
“…These findings further support that objective short sleep duration is a biological marker that predicts both the severity 2 and the natural course of the disorder. 5,6 We agree with Dr Kawada 1 that the use of polysomnographic measures provides strong validity for the findings reported in our study and that future longitudinal studies using longer and multiple followups should further examine the relationship among the natural history of insomnia, objective sleep duration, and cardiovascular risk.…”
supporting
confidence: 86%
“…Individuals with combined insomnia and PSG-defined short sleep duration (<6 hours) have an increased risk of hypertension (Vgontzas et al, 2009a; Fernandez-Mendoza et al, 2012) and Type-2 Diabetes (Vgontzas et al, 2009b), and deficits in executive attention (Fernandez-Mendoza et al, 2010). The presence of PSG-defined short sleep duration (<6 hours) in insomnia is a strong predictor of persistent insomnia years later (Vgontzas et al, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…Short sleep is also recognized to have an adverse effect on hypertension, diabetes, and cardiovascular disease in addition to adverse effects on mental health, including stress, depression or suicide (Cappuccio et al 2011;Kohyama 2011;Vgontzas et al 2012;Gangwisch 2014;Shan et al 2015). Moreover, a prospective cohort study showed that lack of physical activity was linked to worse mental health, with participation in physical activity reported to improve the symptoms of depression (Mammen and Faulkner 2013;Kuwahara et al 2015).…”
Section: Introductionmentioning
confidence: 99%